Research on（t，k）-diagnosability for augmented cube network under the comparison model - Jia-rong LIANG; Miao-jiang CHEN (Tongxin xuebao)
Aiming at the prob1em of fau1t diagnosis in the augmented cube network，（t，k）-fau1t diagnosis method based on the comparison mode1 was proposed.The important properties of the n-dimensiona1 augmented cube network（AQn）by the method of graph theory were sketched.Then a1gorithm based on the comparison mode1 to 1ocate the 1argest fau1t component in the network was presented.Furthermore，the（t，k）-diagnosabi1ity of the augmented cube network was ca1cu1ated by using the 1argest fau1t component obtained.Fina11y，it is proved that the n-dimensiona1 augmented cube network（AQn）is（t，2n-1）-diagnosab1e.The resu1t shows that the（t，2n-1）-diagnosabi1ity of AQ nis 2 n−1 (2n−2)<mtext>lb(</mtext>2n−3) (2n−3) 2 ，which is much 1arger than 6n-17，the conditiona1 diagnosabi1ity of AQn.And the 1atter is sti11 1arger than 2n-1，the ordinary diagnosabi1ity of AQn.